2006
DOI: 10.1111/j.1472-765x.2006.01844.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus isolates on the adhesion of pathogens to chicken intestinal mucus in vitro

Abstract: Aims:  The aims of this study were to investigate in vitro the effects of Lactobacillus isolates from a chicken on adhesion of pathogenic Salmonella and Escherichia coli to chicken intestinal mucus obtained from different intestinal regions. Methods and Results:  Bacteria were labelled by using methyl‐1,2‐[3H]–thymidine. The bacterial adhesion was assessed by measuring the radioactivity of bacteria adhered to the mucus. The results showed that the abilities of Lactobacillus spp. to bind to the same intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…It is possible that the number and type of binding sites for bacteria on mucus may be very different in respect of the enterocyte nature. Curiously, both the studies of Kizerwetter-Świda and Binek (2006) and Ma et al (2006) used natural intestinal tissues of chickens, and the findings were as described previously -they matched the well-established theory of positive inhibitory effect of lactobacilli against pathogens. As to natural microbiota versus probiotics, Garriga et al (1998) found that one strain of L. salivarius was able to colonize and overcome the resident microbiota in the crop and the caecum of the chickens.…”
Section: Probiotic Bacteria In Poultry Productionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is possible that the number and type of binding sites for bacteria on mucus may be very different in respect of the enterocyte nature. Curiously, both the studies of Kizerwetter-Świda and Binek (2006) and Ma et al (2006) used natural intestinal tissues of chickens, and the findings were as described previously -they matched the well-established theory of positive inhibitory effect of lactobacilli against pathogens. As to natural microbiota versus probiotics, Garriga et al (1998) found that one strain of L. salivarius was able to colonize and overcome the resident microbiota in the crop and the caecum of the chickens.…”
Section: Probiotic Bacteria In Poultry Productionmentioning
confidence: 95%
“…Therefore, probiotic strains were predicted to compete for attachment sites, inhibit pathogen adherence and protect the host against infections. This theory of excluded attachment has been proven right in case of L. acidophilus and L. fermentum strains protecting against Salmonella Pullorum and Typhimurium, however not against Salmonella Enteritidis and E. coli in chicken (Jin et al 1998 Ma et al (2006). Moreover, authors suggest that the use of L. acidophilus and L. fermentum mixture may improve the exclusion of Salmonella Typhimurium and E. coli from the chicken GIT to a higher extent than a single species of Lactobacillus.…”
Section: Probiotic Bacteria In Poultry Productionmentioning
confidence: 97%
“…They are commonly used as probiotics, which are defined by the Food and Agriculture Organization/World Health Organization as live microorganisms that, when administered in adequate amounts, confer a health benefit on the host (9). As probiotic agents, lactobacilli can prevent or alleviate infectious diarrhea through their effects on the immune system and promote host resistance to colonization by pathogens (10,11), and many have been shown to adhere to intestinal mucus (12)(13)(14)(15)(16)(17)(18)(19). Confirmation of this lactobacillus-mucus association has not only been observed in vitro, but has also been validated by ex vivo/in vivo microscopic analysis of biopsy samples (20,21).…”
mentioning
confidence: 99%
“…Nearly 70% of the bacterial flora from the intestine of chickens is related to Lactobacillus ( Jiangrang and others 2003). Lactobacillus isolated from the chicken intestine has been shown to play a protective role in excluding pathogenic bacteria in varying degrees from the ileal epithelial cells (Jin and others 1996; Ma and others 2006). In addition, other bacterium isolated from the gastrointestinal tract of poultry has been reported to exhibit strong inhibitory effects on Clostridium spp., Campylobacter spp., and Streptococcus pneumoniae (Alex and Hai‐Meng 2005).…”
Section: Introductionmentioning
confidence: 99%